PEMIKIRAN KEISLAMAN SYAMSUDDIN AS-SUMATRANI TERHADAP TANTANGAN SOSIAL BUDAYA MASYARAKAT MELAYU NUSANTARA - Ramadhani, Sandrina; Donna Takrim; Rahmad Mahadi; Abu Mansur; Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the Islamic thought of Syamsuddin As-Sumatrani and his intellectual responses to the social, cultural, and political challenges faced by the Malay Nusantara society during the 16th–17th centuries. Using a qualitative research method based on library research, this study examines Syamsuddin’s works, classical manuscripts, and relevant modern academic literature. The findings indicate that his thought is rooted in philosophical Sufism, particularly the concept of wahdat al-wujud, which he successfully contextualized within the spiritual landscape of Acehnese and Malay society. Syamsuddin developed a Sufi-based public ethic as a response to emerging social issues resulting from global trade and intercultural interactions. Culturally, he promoted an Islamization model grounded in local wisdom by selecting and reinterpreting Malay customs that aligned with the principles of monotheism. In the political sphere, he emphasized a spiritual-moral model of leadership that prioritizes justice, ethical conduct, and adherence to Islamic law. Overall, this study concludes that Syamsuddin’s ideas are holistic, adaptive, and visionary, effectively addressing the societal challenges of his time while remaining relevant to contemporary Islamic discourse in the Nusantara region.